2015
DOI: 10.1021/acs.macromol.5b00060
|View full text |Cite
|
Sign up to set email alerts
|

Long-Spaced Polyamides: Elucidating the Gap between Polyethylene Crystallinity and Hydrogen Bonding

Abstract: Aliphatic polyamides with so far inaccessibly low amide contents were prepared by acyclic diene metathesis (ADMET) copolymerization of N-(undec-10-en-1-yl)undec-10-enamide (1) and undeca-1,10-diene (2) applying different Grubbs and Hoveyda−Grubbs type olefin metathesis catalyst precursors, followed by exhaustive postpolymerization hydrogenation to yield saturated copolymers. These polyamides, containing between 1.0 and ca. 50.5 amide groups per 1000 methylene units, fill the gap between polyamides from classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 70 publications
3
36
0
Order By: Relevance
“…In most cases, a glass transition point was either not detectable or outside the measured range (minimum −100 °C). While the non-hydrogenated polymers are either amorphous or show a T m below room temperature, the hydrogenated polymers have T m up to 117 °C for poly( 2 ) 1 - co -COD 9 , which is similar to completely linear PE with 134 °C 6 (cf. Figure 3C shows the DSC thermogram of poly( 3 ) 1 - co -COD 9 with T m = 109 °C).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In most cases, a glass transition point was either not detectable or outside the measured range (minimum −100 °C). While the non-hydrogenated polymers are either amorphous or show a T m below room temperature, the hydrogenated polymers have T m up to 117 °C for poly( 2 ) 1 - co -COD 9 , which is similar to completely linear PE with 134 °C 6 (cf. Figure 3C shows the DSC thermogram of poly( 3 ) 1 - co -COD 9 with T m = 109 °C).…”
Section: Results and Discussionmentioning
confidence: 99%
“…where V is the volume of the specimen (cm 3 ), m1 and m2 are the mass of the specimen (g) in air and water, respectively, and ρH2O is the density of water (1 g•cm 3 ). The mass of the object in air was then divided by this calculated volume to yield the density.…”
Section: Density Measurementsmentioning
confidence: 99%
“…These PAs possess a range of attractive properties, including high mechanical strength, good solvent stability/resistance, lower melting temperatures and low moisture absorption 3,4 . In particular, reduced moisture absorption gives long-chain PAs a competitive edge over their shorter-chain counterparts, such as PA 6 and PA 6,6.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same C20 diester monomer, also renewable polyesteramides with adjustable thermal properties were described . An even longer amide spacing in aliphatic polyamides was achieved by the copolymerization of the renewable N ‐(undec‐10‐en‐1‐yl)undec‐10‐enamide with undeca‐1,10‐diene in different ratios via ADMET polymerization and hydrogenation, leading to polyamides containing between 1 and 50 amide groups per 1000 methylene units . The authors observed that the melting points of these polyamides converged toward one of polyethylene the lower the amide group content got.…”
Section: Polyamidesmentioning
confidence: 99%